THE LEGAL PROTECTION OF MINORITY SHAREHOLDERS AGAINST COMPANY CONSOLIDATION IN THE PERSPECTIVE OF THE LIMITED LIABILITY COMPANY LAW - Novanda, Ni Putu Rosita; Mahendrawati, Ni Luh Made; Styawati, Ni Komang Arini (jfpublisher, 2025)
Company consolidation is one of the legal actions that can significantly impact shareholders, predominantly minority shareholders. Law No. 40/2007 on Limited Liability Companies (UUPT) stipulates that in the consolidation process, the rights of minority shareholders must still be considered, including the right to request the purchase of their shares at a fair price if they disagree with the decision of the General Meeting of Shareholders (GMS). However, in practice, implementing legal protection for minority shareholders still faces various challenges, especially regarding legal certainty and the mechanism for exercising their rights. This research aims to provide a comprehensive understanding of the legal landscape surrounding minority shareholders in the context of company consolidations, highlighting both existing protections and areas needing reform. This research uses normative legal research methods with statutory and conceptual approaches. The results show that although Article 62 of the UUPT gives minority shareholders the right to sell their shares to the company in certain situations, the absence of clear sanctions for companies that fail to carry out this obligation causes legal uncertainty. Therefore, a firmer legal reconstruction is necessary, including providing administrative sanctions and compensation for companies that do not fulfil their obligations. In addition, dispute resolution mechanisms can be implemented through litigation and non-litigation channels, such as mediation and arbitration, to provide more effective protection for minority shareholders.